The Alphabetic Acrostic in Book I of the Psalms: An Overlooked Element of Psalter Structure - Robertson, O. Palmer (Journal for the study of the Old Testament, 2015)
Studies of acrostic psalms have generally overlooked their structural contribution to the Psalter. By offering a close analysis of the placement of these psalms, this article shows that the eight acrostics all occur in Books I and V, and nicely divide these two largest Books into smaller segments. With respect to Book I, this article argues (1) that the acrostic Psalms 34 and 37 bracket four psalms of the innocent sufferer, followed by four psalms of the innocent sufferer; (2) that the three creation psalms of Book I immediately precede an acrostic psalm, with creation Psalm 8 preceding acrostic Psalm 9/10, creation Psalm 24 preceding acrostic Psalm 25, and creation Psalm 33 preceding acrostic Psalm 34; and (3) that the appearance within acrostic Psalm 9/10 of various acrostic types suggests that the editor(s) of the Psalter may have intended this initial acrostic to provide the reader with a sampler of acrostic forms.